Real-time blood gas management: evaluating quantum perfusion system’s accuracy against a standard blood gas analysis in CPB - Bahi Hyasat; Amjad Bani Hani; Ali Al Saraireh; Rana Al Kirmeen; Dina Sabha; Saif Yamin; Islam Massad; Ayman Hammoudeh (Journal of Cardiothoracic Surgery)
Abstract Background Continuous blood gas monitoring (CBGM) during cardiopulmonary bypass (CPB) is essential for maintaining optimal patient outcomes, enabling rapid responses to critical fluctuations in blood gas parameters. This non-inferiority study evaluates the Quantum Perfusion System by Spectrum Medical, which features continuous online blood gas monitoring through Quantum workstation (QWS) and Quantum ventilation module (QVM) without the use of cuvettes, against the standard blood gas analysis (BGA) analyzer to assess real-time clinical accuracy. Methods This retrospective study included a sample of 40 patients, monitored continuously with the QPS and compared at intervals against standard BGA measurements. The patients undergoing on elective CPB procedures, specifically for coronary artery bypass grafting (CABG), mitral valve replacement (MVR), and aortic valve replacement (AVR). Results Pre-alignment deviations for all parameters were within CLIA thresholds, confirming baseline reliability. For hemoglobin, the pre-alignment deviation was 1.9%, which decreased to 0.7% post-alignment, both within the CLIA threshold of ± 5%, with a Bland-Altman mean difference of 0.0988 g/dL (limits: 0.0963 to 0.1012 g/dL). Hematocrit showed a pre-alignment deviation of 2.1%, reduced to 0.2% post-alignment, both within the CLIA threshold of ± 5%, with a Bland-Altman mean difference of 0.3009% (limits: 0.2956 to 0.3063%). For PaO₂, the pre-alignment deviation was 3.9%, reduced to 0.4% post-alignment, both within the CLIA threshold of ± 10%, with a Bland-Altman mean difference of 4.0490 mmHg (limits: 3.9976 to 4.1004 mmHg). PCO₂ demonstrated a pre-alignment deviation of 4.2%, reduced to 0.19% post-alignment, both within the CLIA threshold of ± 10%, with a Bland-Altman mean difference of 0.3790 mmHg (limits: 0.3751 to 0.3829 mmHg). SvO₂ showed a pre-alignment deviation of 3%, which decreased to 0.8% post-alignment, both within the CLIA threshold of ± 5%, with a Bland-Altman mean difference of 0.7782% (limits: 0.7706 to 0.7858%). Finally, for SaO₂, the pre-alignment deviation was 2.6%, reduced to 0.1% post-alignment, both within the CLIA threshold of ± 5%, with a Bland-Altman mean difference of 0.9614% (limits: 0.9594 to 0.9634%). The Passing-Bablok regression analysis confirmed strong agreement, with slopes close to 1.0100 and intercepts near zero for all parameters. These results validate the QPS as a reliable and non-inferior tool for real-time blood gas monitoring during cardiopulmonary bypass, adhering to CLIA standards and ensuring clinical accuracy. Conclusions The findings support the accuracy of the Quantum Perfusion System compared to the BGA standard, demonstrating the system’s capability to provide accurate, continuous blood gas monitoring during CPB. However, further studies are necessary to strengthen and confirm these results across broader and more varied clinical scenarios, for these reason as recommended by the manufacturers, the quantum monitoring system should only be used as a trending device.